TEACHING WRITING BY USING GUIDING QUESTION TECHNIQUE AT THE TENTH GRADE STUDENTS OF SMA NEGERI 2 RANTEPAO - Meiska Salu Bongga Rante; Yizrel Nani Sallata (Teaching English as a Foreign Language Overseas Journal, 2022)
The objective of this research is to find out whether or not the guiding questions technique is effectively used in writing descriptive text for the tenth grade students of SMA Negeri 2 Rantepao. This research used cluster sampling, the population of this research was the tenth grade students of SMAN 2 Rantepao academic year 2018/2019. It consisted of 360 students. Because the population was quite large, the writer chose one class that consists of 30 students as a sample. The data were collected through a written test as the instrument. To analyze the data the researcher used SPSS 21. The result of this research shows that the Guiding Question Technique effectively used in Writing Descriptive Text at the tenth grade students of SMA Negeri 2 Rantepao” It can be proved by the value of t-test and t-table. Based on the finding, the value of t-test is higher than t-table (16.155>2.04523), which means that an alternative hypothesis is accepted. It can be concluded that Guiding Question Technique effective used in Writing Descriptive Text at the tenth grade students of SMA Negeri 2 Rantepao”